An ARFID case report assessment with 18F-FDG PET/MRI and treatment with olanzapine, escitalopram and fluoxetine in adult - Liu, Meichen; Chang, Yiheng; Xie, Xueting; Liu, Yudan; Tian, Shiyun; Yang, Chun; Zhao, Ziqi; Zhang, Huimin (Frontiers in Psychiatry, 2025)
BackgroundAvoidant/restrictive food intake disorder (ARFID), a DSM-5-introduced eating disorder, is increasingly prevalent and challenging to treat, primarily affecting children and adolescents, with limited adult case reports. This rarity in adults leads to misdiagnosis or underdiagnosis, and treatment experiences are scarce.Case presentationThis report details an adult ARFID case, where the patient’s fear of food intake followed gastric damage from corn ingestion, resulting in a restrictive diet of rice porridge due to gastric pain. The behavior is driven by fear of eating-related adverse effects.ResultBased on clinical symptoms assessment, semi-structured interviews, and comprehensive testing, including PET/MRI scans to exclude secondary conditions, a diagnosis of ARFID was confirmed. ARFID, a newly introduced diagnosis in the DSM-5, is uncommon in adults with sparse case data. Differentiating it from gastrointestinal diseases and other psychiatric conditions is crucial for precise diagnosis and focused treatment.ConclusionIn this paper, we report on the clinical diagnosis, imaging manifestations, treatment, and follow-up of an adult ARFID case, highlighting the utility of neuroimaging in diagnosis and differentiation. It also assesses the therapeutic efficacy of olanzapine, escitalopram oxalate, and fluoxetine hydrobromide, offering clinical guidance for diagnosing and managing ARFID.